Correction: Disease-specific protein corona sensor arrays may have disease detection capacity. Issue 2 (8th January 2020) - Caracciolo, Giulio; Safavi-Sohi, Reihaneh; Malekzadeh, Reza; Poustchi, Hossein; Vasighi, Mahdi; Chiozzi, Riccardo Zenezini; Capriotti, Anna Laura; Laganà, Aldo; Hajipour, Mohammad; Di Domenico, Marina; Di Carlo, Angelina; Caputo, Damiano; et al.
Abstract : Correction for 'Disease-specific protein corona sensor arrays may have disease detection capacity' by Giulio Caracciolo et al., Nanoscale Horiz., 2019, 4, 1063–1076.